Optimalisasi Pemanfaatan Sumber Daya Lokal Berbasis Pengolahan Pangan di Desa Mantingan, Kecamatan Jaken, Kabupaten Pati - Muhammad Aushol Amri; Aisyah Nurrismiyandini; Mellania Chandra Dewi; Ika Feby Astuti; Sumi Jayanti; I Wayan Astika (Jurnal Pusat Inovasi Masyarakat (PIM), 2021)
Community empowerment needs to be realized to increase the independence of village communities. Community empowerment activities in the village of Mantingan, especially KWT Al-Ikhlas, can improve knowledge and skills related to the processing of chili and shallot agricultural products, as well as take advantage of the telang flower which is rich in benefits. The method of implementation is carried out in several activities, namely discussions with partners, trials of making chili and siwang powder, training in making chili and siwang powder, planting telang flowers, and making agricultural product brands. The community prefers to sell chilies and shallots directly to collectors even when the price of chilies and shallots drops. The community considers the telang plant to be a wild plant because they do not know the benefits of the telang flower. Making chili powder is done to overcome the price of chili which tends to fluctuate and extend the self-life of the chilies being harvested. The innovation in processing chili powder "Mak Chilli Tini" and "Siwang Mak Tini" onion paste has a large potential profit margin. The chili powder product "Mak Chilli Tini" and the onion paste "Siwang Mak Tini" have a lower selling price per gram than other products and PIRT certificates, so the optimism to legally compete with the broad market is high. Socialization about the benefits of telang flowers has made the people of Mantingan Village more familiar with telang flowers and are interested in planting them. Telang plants were distributed to 44 residents of Mantingan Village. This activity helps the people of Mantingan Village to solve 2 main problems, namely the fluctuating price of chilies and shallots in the market and the problem of marketing KWT commodities that have not been maximized. Keywords: chilies, shallots, siwang, telang